Implementasi Pembelajaran Literasi dan Numerasi Berbasis Kurikulum Merdeka di Kelas IV SD Negeri 007 Bangkinang: Penelitian - Nurhaswinda; Amaliah Fitriani; Arzila Putri; Diana Prorida; Okti Valensi; Putri Anggraini; Trisya Anjani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The purpose of this study is to implement literacy and numeration study with a merdek curriculum based, which is performed in the fourth grade of the country's elementary school of chai bangkinang during the learning process. In this study will qualitative assessments of the application of literacy and numeration study. A qualitative case study approach using descriptive methods is used in this study asa method to understand the problem, data is collected through interviews, observation, and documentation. Studies indicate that the implementation of literacy and numeration study works, even well and smoothly. Based on the interviews obtained, there are challenges faced in imstructurization, as one of the implementation of the implementation requires adjusted room conditions, a limited facility. It can also be seen from the number of students in learning groups, as well as learning methods that can improve learning so that learning becomes effective using free curriculum.